Teachers' Daily Negative Emotions in Interactions With Individual Students in Special Education. (March 2019) - Koenen, Anne-Katrien; Vervoort, Eleonora; Kelchtermans, Geert; Verschueren, Karine; Spilt, Jantine L.
To understand and support teacher–student interactions, there is a need for research on teachers' daily emotions in interactions with students. Therefore, this study investigated the development of teachers' negative emotions in interactions with individual students with attachment problems. Using a 3-week diary study, data were collected from 71 teacher–student dyads in special education schools for students with emotional and behavioral disorders. Overall, the development of both activating (e.g., anger) and deactivating (e.g., helplessness) negative emotions was low and stable over time. Teachers with high self-efficacy and teachers with a high supportive teaching style were less likely to experience intensity of and variability in negative emotions. Student maladjustment and teachers' depersonalization attitudes were positively associated with more activating negative emotions. Beginning teachers reported more deactivating negative emotions. The study highlights the need of emotion-focused interventions for teachers to promote positive interactions between teachers and individual students.